Examining key challenges in the programmes of adult community learning centres in KwaZulu-Natal. Issue 2 (November 2022) - Akintolu, Morakinyo; Uleanya, Chinaza; Letseka, Moeketsi
Education is a major tool for development and equalizer. This somewhat accounts for the quest for education, at various levels, including adults who were unable to attain an education degree earlier in life. Thus, Adult Education and Training (AET) programmes are established in different community centres to promote adult literacy in different parts of the world inclusive of South Africa. However, many AET community centres tend not to be achieving the aim for their establishment due to various challenges. Hence, this study examined the challenges that are facing adult community learning centres using KwaZulu-Natal Province of South Africa following that it has one of the highest rates of illiteracy that causes unemployment and poverty. Social Cognitive Theory was employed for theoretical framework. Qualitative method was adopted for the study; hence, face-to-face interviews were conducted for nine purposively selected centre managers from both rural and urban KwaZulu-Natal. The collected data was coded and thematically analysed. The findings show that adult learners, facilitators and government factors inhibit the community learning centres progress. Meanwhile, centre managers strive to support adult community learning by involving different stakeholders in adult education and prioritize same. The study recommends amongst others the adoption of systemic approach where visions of AET are clearly stated to all stakeholders such as learners, facilitators, and the government.